CPER field day, August 24, 1990 - Shortgrass Steppe Long Term Ecological Research (SGS-LTER), author (Colorado State University. Libraries, 1990)
Research at the site on the CPER is being conducted by the ARS Hydro-Ecosystem Research Unit in cooperation with the LTER program on the Shortgrass Steppe. The objective of hydrology research being conducted by the Hydro-Ecosystem Research group of the ARS at CPER in cooperation with the CPER/LTER project is to validate a spatially explicit hydrologic simulation model for semiarid grassland, and to provide long-term observation of hillslope hydrologic processes. The research involves both natural runoff plots and rainfall simulation studies.
Hydrology at the CPER
SGS-LTER 1990 CPER hydrology trip
The SGS-LTER research site was established in 1980 by researchers at Colorado State University as part of a network of long-term research sites within the US LTER Network, supported by the National Science Foundation. Scientists within the Natural Resource Ecology Lab, Department of Forest and Rangeland Stewardship, Department of Soil and Crop Sciences, and Biology Department at CSU, California State Fullerton, USDA Agricultural Research Service, University of Northern Colorado, and the University of Wyoming, among others, have contributed to our understanding of the structure and functions of the shortgrass steppe and other diverse ecosystems across the network while maintaining a common mission and sharing expertise, data and infrastructure.
Keywords: grassland ecology; long term ecological research; shortgrass steppe; Central Plains Experimental Range; Pawnee National Grassland